2023
DOI: 10.3390/v15030777
|View full text |Cite
|
Sign up to set email alerts
|

Immune Molecules’ mRNA Expression in Porcine Alveolar Macrophages Co-Infected with Porcine Reproductive and Respiratory Syndrome Virus and Porcine Circovirus Type 2

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus 2 (PCV2) are economically important pathogens in swine, and pigs with dual infections of PCV2 and PRRSV consistently have more severe clinical symptoms and interstitial pneumonia. However, the synergistic pathogenesis mechanism induced by PRRSV and PCV2 co-infection has not yet been illuminated. Therefore, the aim of this study was to characterize the kinetic changes of immune regulatory molecules, inflammatory factors and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…This might be indicative of the commencement of recovery mechanisms in pigs from PRRS, suggesting a potential temporal modulation of these genes during the infection’s progression. These findings align with three other investigations, which report CTLA4 upregulation during PRRSV-1 or PRRSV-2 infection ( 59 61 ), lending further credence to the prolonged immune suppressive effect of PRRSV. We also observed the upregulation of another gene, SAMHD1 (SAM domain and HD domain-containing protein 1), known for its antiviral properties triggered by interferon, and its capacity to restrain the proliferation of numerous RNA or DNA viruses ( 62 , 63 ).…”
Section: Discussionsupporting
confidence: 90%
“…This might be indicative of the commencement of recovery mechanisms in pigs from PRRS, suggesting a potential temporal modulation of these genes during the infection’s progression. These findings align with three other investigations, which report CTLA4 upregulation during PRRSV-1 or PRRSV-2 infection ( 59 61 ), lending further credence to the prolonged immune suppressive effect of PRRSV. We also observed the upregulation of another gene, SAMHD1 (SAM domain and HD domain-containing protein 1), known for its antiviral properties triggered by interferon, and its capacity to restrain the proliferation of numerous RNA or DNA viruses ( 62 , 63 ).…”
Section: Discussionsupporting
confidence: 90%
“…This finding complements earlier reports showing that coinfection with PCVs may favor the development or enhance the course of the other diseases [36]. Swine circoviruses have tropism to the lymphoid tissue of the host, thereby leading to immunosuppression and an increased tendency to secondary infections [41]. Moreover, it has been demonstrated that PCV2 and PRRSV coinfection promoted PRRSV replication in PAM cells.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, it has been demonstrated that PCV2 and PRRSV coinfection promoted PRRSV replication in PAM cells. The downregulation of immune regulatory factors (IFN-α and IFN-γ) and the upregulation of inflammatory factors (TNF-α, IL-1β, IL-10, and TGF-β) and immune checkpoint molecules (PD-1, LAG-3, CTLA-4, and TIM-3) were observed in the cells where PRRSV infection was preceded by PCV2 [41]. Consistent with these reports, our results suggest that primary PCV3 infection, similar to PCV2, may play a role in susceptibility to the other viruses, including ASFV.…”
Section: Discussionmentioning
confidence: 99%